2019
DOI: 10.1093/jnci/djz106
|View full text |Cite
|
Sign up to set email alerts
|

Annual Report to the Nation on the Status of Cancer, Featuring Cancer in Men and Women Age 20–49 Years

Abstract: Background The American Cancer Society, Centers for Disease Control and Prevention, National Cancer Institute, and North American Association of Central Cancer Registries provide annual updates on cancer occurrence and trends by cancer type, sex, race, ethnicity, and age in the United States. This year’s report highlights the cancer burden among men and women age 20–49 years. Methods Incidence data for the years 1999 to 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(218 citation statements)
references
References 85 publications
(89 reference statements)
5
203
2
8
Order By: Relevance
“…Among AYAs, the increase in female breast cancer incidence rates during 2010 through 2016 after a period of stability is concerning—particularly because death rates, which had declined during 2001 through 2010, also began to stabilize in 2010. As noted in last year's report, opportunities for primary prevention of breast cancer among younger and premenopausal women are limited . More detailed studies may help evaluate potential reasons for these adverse trends.…”
Section: Discussionmentioning
confidence: 99%
“…Among AYAs, the increase in female breast cancer incidence rates during 2010 through 2016 after a period of stability is concerning—particularly because death rates, which had declined during 2001 through 2010, also began to stabilize in 2010. As noted in last year's report, opportunities for primary prevention of breast cancer among younger and premenopausal women are limited . More detailed studies may help evaluate potential reasons for these adverse trends.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, advances in cancer research have led to great improvements in the prevention, early detection, and treatment of cancer. This progress has been reflected in a continuous decline in overall cancer death rates and gradual increases in cancer survival . However, cancer death rates have not declined at the same pace for all cancer types or in all sociodemographic groups, indicating that communities in the United States have not benefited equally from initiatives to reduce the cancer burden.…”
Section: Discussionmentioning
confidence: 99%
“…All six studies from the USA consistently reported increasing incidence between 2011 and 2015 (28) or over recent decades (23)(24)(25)(26)(27). These increases were evident among persons (23,24,26) and by sex (23,25,27,28). In Colombia, trends increased in males but were stable among females from 2008 to 2012 (29).…”
Section: Liver Cancers Combinedmentioning
confidence: 97%